2020
DOI: 10.3390/brainsci10110874
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the T2–FLAIR Mismatch Sign as an Imaging Marker of IDH Status in a Mixed Population of Low- and High-Grade Gliomas

Abstract: Our study evaluated the role of the T2–fluid-attenuated inversion recovery (FLAIR) mismatch sign in detecting isocitrate dehydrogenase (IDH) mutations based on a mixed sample of 24 patients with low- and high- grade gliomas. The association between the two was realized using univariate and multivariate logistic regression analysis. There was a substantial agreement between the two raters for the detection of the T2–FLAIR mismatch sign (Cohen’s kappa coefficient was 0.647). The T2–FLAIR mismatch sign when co-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Broen et al confirmed the 100% positive predictive value (PPV) for the T2-FLAIR mismatch sign in predicting IDHmut-noncodel astrocytoma in a multi-institution cohort of LGG (30). Moreover, recent studies have shown that IDH mutation status is related to the T2-FLAIR mismatch sign (31,32). Therefore, the T2-FLAIR sign was included in the present study.…”
Section: Discussionmentioning
confidence: 54%
“…Broen et al confirmed the 100% positive predictive value (PPV) for the T2-FLAIR mismatch sign in predicting IDHmut-noncodel astrocytoma in a multi-institution cohort of LGG (30). Moreover, recent studies have shown that IDH mutation status is related to the T2-FLAIR mismatch sign (31,32). Therefore, the T2-FLAIR sign was included in the present study.…”
Section: Discussionmentioning
confidence: 54%
“…Various studies differ in the significance of the mismatch alongside other parameters. Kapsalaki et al reported that implementing additional co-registration imaging parameters have no significance in improving the diagnostic accuracy of the mismatch sign [ 9 ]. Another study found that mismatch sign has no correlation with symptoms, preoperative, and postoperative volume, type, and extent of surgery or survival [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because the range of gliomas may be mismatched on T2WI and FLAIR images, especially for high-grade gliomas ( 30 ), the radiomic features derived from the two sequences may be different. It has been reported that DMG-M is a distinct subtype of isocitrate dehydrogenase (IDH) wild-type glioma ( 31 ), and that the co-deletion of IDH and 1p/19q are related to T2-FLAIR mismatch ( 30 , 32 , 33 ). Accordingly, we speculate that stratification analysis according to molecular status (such as the presence of an IDH mutant) or T2-FLAIR mismatch may be useful for distinguishing DMG-M and DMG-W tumors, and this therefore warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%